Influence of Sliding Speed on the Tribological Characteristics of Pongamia Oil with Tio2 Nanoparticles - Singh, Yashvir; Sharma, Abhishek; P. Dwivedi, S.; R.Mishra, V.; Kumar Srivastava, Ashish (International Journal of Engineering and Technology, 2018)
Environment degradation and non-biodegradability are the major problems associated with mineral-oil based lubricants. Non-edible vegetable oils are one of the suitable substitutes for the mineral oils. In this study, pongamia oil was used as the lubricant to check its feasibility for the tribological behaviour. TiO2 nanoparticles are added to the pongamia oil on a weight-percentage basis. The variation of TiO2 nanoparticles concentration with pongamia oil was evaluated for the coefficient of friction and wear analysis.Â Minimum coefficient of friction and wear was observed at 0.1 % concentration which gets further increased at 0.2 % concentration. The smooth surface of the pin was observed at 0.1 % nanoparticles concentration with the comparison to base pongamia oil.Â Â Â